Role of extracorporeal membrane oxygenation in pediatric myocarditis - Tran, Kiem Hao; Nguyen, Dac Luong; Pham, Kieu Loc; Ho, Dang Quan; Vo, Van Nguyen Loi; Tran, Hoang; Nguyen, Ngoc Minh Chau (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Fulminant myocarditis in children is rare, but it has the potential for high morbidity and mortality. In this report, we review articles demonstrating the role of venoarterial extracorporeal membrane oxygenation (VA-ECMO) in the fulminant myocarditis, and describe the clinical course of a healthy 11-year-old girl who rapidly deteriorated into cardiogenic shock. The patient was weaned from mechanical ventilation on day 7 and she was discharged from the ICU on day 12. VA-ECMO is considered as a life-saving therapy in patients with hemodynamic instability prior to recovery or other escalation therapy.